Respuestas

2012-05-20T01:02:22+02:00

El sucesor de n es (n + 1).

 

El doble del sucesor es 2(n + 1).

 

Al sumar ambos, se tiene:

 

n + 2(n + 1) = 44

 

==> n + 2n + 2 = 44

==> 3n = 44 -2

==> 3n = 42

==> n = 42 / 3

==> n = 14

 

Asi que, (n + 3) = 14 +3 = 17


2012-05-20T01:54:33+02:00

El sucesor de n es (n + 1).

 

El doble del sucesor es 2(n + 1).

 

Al sumar ambos, se tiene:

 

n + 2(n + 1) = 44

 

==> n + 2n + 2 = 44

==> 3n = 44 -2

==> 3n = 42

==> n = 42 / 3

==> n = 14

 

Asi que, (n + 3) = 14 +3 = 17